Occurrence and Distribution of Sarcocystis Parasite Isolated from Sheep in Yazd Province, Iran - Bahador Hajimohammadi; Amin Zohourtabar; Ali Fattahi Bafghi; Azam Omidpanah; Tayebe Rayati; Abolfazl Ghasemi; Alireza Sazmand (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: Sarcocystis species are one of the most important meat borne parasites. Sarcocystosis causes several symptoms in human as well as numerous diseases with high economic impact in livestock. In current paper at first results of a pilot study for determination of disease agent in lamb of Yazd province central Iran is presented. Then status of parasite in red meat products in study region gets discussed. Materials and Methods: Muscles of 70 slaughtered Sheep from both sexes and different ages were investigated for presence of parasite cysts during September to October 2013. Carcass inspection with naked eye at industrial slaughterhouse of Yazd for macroscopic cysts, and pepsin-digestion method for microscopic cysts was performed on common infected sites of infection. Results: No macroscopic cyst was seen at inspection, however bradyzoites of parasite were observed in 97.14% of animals' digested muscles. No significant difference between infection and age groups or sex of animals was observed. Conclusion: As humans are considered as final and intermediate host of different species of Sarcocystis, and parasite cysts present at microscopic sizes, transmission of infection from lamb meat should come into consideration. Hence public training of disease health importance, parasite cycle and methods of inactivation probable cysts in meat is recommended.